Designing, implementing, and evaluating an introductory course on virtual learning in the Covid-19 pandemic era - Mahsa Shakour (Journal of Medical Education Development, 2022)
Background & Objective: The sudden outbreak of Covid-19 affected the educational systems worldwide and highlighted the necessity of students' virtual education. Therefore, the present study aimed to compile, implement, and evaluate an introductory course on virtual learning for medical students. Materials & Methods: The present scholarly research was conducted in four stages: 1) needs assessment and establishment of objectives, 2) content determination, 3) implementation, and finally, 4) evaluation of the program at Arak University of Medical Sciences in the years 2020-2021. Needs assessment data were obtained via structured interviews and focus group meetings for 30 students and 12 professors. The content was produced for each purpose and uploaded on the Navid system for training. The first two levels of the Kirkpatrick model were used for evaluation. A researcher-made questionnaire was employed and electronically distributed to assess the level of students' satisfaction. Results: Based on the results, the mean scores of students' satisfaction and learning were 18.43±1.5 and 16.8±2.5 out of 20, respectively. Conclusion: The curriculum developed in this study for first-semester students can increase their knowledge of virtual education methods and satisfaction during the Covid-19 and Post-COVID-19 era.